Pengaruh Pembelajaran Produk Kreatif Kewirausahaan dan 21 st-Century Digital Skills terhadap Minat Berwirausaha Pada Peserta Didik SMK - Venny, Sisilia; Asriati, Nuraini; Syamsuri, Syamsuri (Jurnal Ilmiah Dikdaya, 2023)
This research aimed to determine the effect of Entrepreneurial Creative Product learning and 21 st- Century Digital skills on Vocational High School of Immanuel Christian II Sungai Raya students. This study employed a causal or causal relationship method using a quantitative approach. The study’s subject comprised twelfth-grade students, and the data was collected through questionnaires administered to twelfth-grade students. (1) The direct effect of Entrepreneurial Creative Product learning on entrepreneurial interest was moderate, at 35.9%. (2) The direct effect of 21 st-century digital skills on entrepreneurs' interests was moderate, at 30.6%. (3) The direct effect of Entrepreneurial Creative Product learning on 21 st-century digital skills was moderate, at 39.3%. (4) Learning creative entrepreneurial products affected entrepreneurial interest through 21 st-century digital skills in Vocational High School of Immanuel Christian II Sungai Raya students with mediation status was partial mediation indicating that direct effect and indirect effect were accepted.